PC-SWMM modeling of policy changes on suburban watersheds in Johnson County, Kansas - Brady, Grant (Kansas State University, 2015)
Urban areas have traditionally been managed as separate entities from the natural environment. Recently, urban planners have been interested in reconnecting these areas back to the biosphere to capitalize on ecosystem services restoring damaged hydrologic processes. This study focuses on suburban Johnson County, KS (part of the Greater Kansas City area), which has 62 USEPA 303(d) listed “impaired” or “potentially impaired” waterbodies. Previous studies show that watersheds crisscrossed by multiple politically boundaries see increases in water quantity and decreases in water quality. Using a multi-watershed, multi-city spanning entity like a school district, it is investigated how stormwater best management practices (BMPs) employed over a large entity can help undo the negative effects of watershed political fragmentation. BMP modeling includes simulating grassroots and planning policy change movements across three target watersheds using PC-SWMM watershed model. The grassroots simulation models rain barrels at single family homes and an extended dry detention basin (EDDB) at schools. Planning policy simulation models 10% and 20% reductions in impervious roads and parking lots in accordance to EPA Smart Growth practices. Resulting, it was seen that all three of these BMPs saw the greatest improvements from current conditions at low precipitation events. Ranking from least to most effective across the outlet’s average flow, maximum flow, and total volume and supporting watershed infiltration, surface runoff, and surface storage are as follows: rain barrels + EDDB, 10% reduced, and 20% reduced impervious simulations. All three stormwater BMPs help demonstrate how grassroots movements and planning polices changes can positively impact regional waterbodies in this maturely suburbanized region.
Keywords: Water resources; Watershed modeling; SWMM; Stormwater management; Smart growth; Environmental education (0442); Environmental Engineering (0775); Environmental management (0474); Land Use Planning (0536); Urban Planning (0999); Water Resource Management (0595)